1988
DOI: 10.1007/bf00442614
|View full text |Cite
|
Sign up to set email alerts
|

The effect of L-asparaginase on lipid metabolism during induction chemotherapy of childhood lymphoblastic leukaemia

Abstract: L-asparaginase is an effective antileukaemic drug and a potent inhibitor of hepatic protein synthesis. Its effect on lipid metabolism was studied in two cohorts of children with ALL, one of whom received L-asparaginase concomitantly with three other drugs (protocol BFM 79). In the second protocol (BFM 83) administration of L-asparaginase was arranged to follow the other three drugs in time sequence. The two major findings of this study were elevated serum levels of total cholesterol and a strong increase in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…Further long-term clinical trials are needed to assess the benefits, risks, limitations, and cost-effectiveness of universal and comprehensive childhood cholesterol screening. 370 Among different treatment modalities for childhood cancers (Table 1), radiation exposure in the presence or absence of GH deficiency 276,366 and treatment with corticosteroids 371,372 have been proposed as possible mechanisms leading to the abnormal lipid profile in cancer survivors. A number of chemotherapeutic agents have also been implicated in dyslipidemia.…”
Section: Lipid Abnormalitiesmentioning
confidence: 99%
“…Further long-term clinical trials are needed to assess the benefits, risks, limitations, and cost-effectiveness of universal and comprehensive childhood cholesterol screening. 370 Among different treatment modalities for childhood cancers (Table 1), radiation exposure in the presence or absence of GH deficiency 276,366 and treatment with corticosteroids 371,372 have been proposed as possible mechanisms leading to the abnormal lipid profile in cancer survivors. A number of chemotherapeutic agents have also been implicated in dyslipidemia.…”
Section: Lipid Abnormalitiesmentioning
confidence: 99%
“…The proposed mechanisms of ASP-induced HTG are decreased lipoprotein lipase activity (15), which may result in elevated exogenous chylomicrons (16), and increased endogenous very-low-density lipoprotein (VLDL) synthesis (5). Additionally, it's been suggested that ASP may cause a disturbance in lipoprotein metabolism (17).…”
Section: Discussionmentioning
confidence: 99%
“…The latter showed a significant increase of TG and chylomicrons but not of total cholesterol. The authors concluded that ASP was responsible exclusively for the increase of TG, likely by the enrichment of exogenous chylomicrons (16). Furthermore, Parson reported an elevation of TG mainly due to endogenous VLDL production during ASP therapy and increased cholesterol while receiving steroids (5).…”
Section: Discussionmentioning
confidence: 99%
“…While many patients have had elevation in blood ammonia levels, but a correlation between ammonia levels and degree of toxicity has not been firmly established. Cremer et al [173] studied the effect of l-asparaginase on lipid metabolism during induction chemotherapy of childhood lymphoblastic leukemia and found changes in serum lipid. An account of comparative induction toxicity of native and PEG-l-asparaginase has been tabulated in Table 7.…”
Section: Toxicitymentioning
confidence: 99%